THE STUDY OF PULMONARY TUBERCULOSIS IN DIABETES MELLITUS PATIENTS - HARIPRASAD S; RAMAKRISHNA M R; TRUPTI R R; SREEKANTHA; AVINASH S S; VINODCHANDRAN (International Journal of Pharma and Bio Sciences, 2013)
Clinical and radiological study of pulmonary tuberculosis in diabetic patients. METHODS: 100 cases of diabetes mellitus with pulmonary tuberculosis were studied.Their clinical profile and chest radiograph results were analyzed. RESULTS: The predominant clinical symptoms noted were anorexia (80%), cough (73%), fever (56%). 62.5% of male patients were smokers.Clubbing was noted in 10% of our patients. Average duration of diabetes was 6.6 years. 51% of patients were anemic and 52% of patients had an erythrocyte sedimentation rate above 50mm/hr. The average FBS value was 234.4 mg/dl. 81% of patients were sputum positive for acid fast bacilli under the age of 40 years. Cavitary lesions were noted in about 53% of patients. 38% of patients had infiltration. Fibrosis was noted in 37% of patients above 40 years. Lower lung field involvement was noted in 32% of patients and was more common in patients greater than 40 years. INTERPRETATION AND CONCLUSION: Multiple cavities and multiple lobe involvement are more common in tuberculous diabetics and lower lung field is involved more commonly in older age group patients.Severe hyperglycemia appears to be a contributory factor to the development of pulmonary tuberculosis in diabetics.Diabetes appears to have no effect on the presenting features of pulmonary tuberculosis to a large extent.